2021
DOI: 10.1681/asn.2020071097
|View full text |Cite
|
Sign up to set email alerts
|

Risks of AKI and Major Adverse Clinical Outcomes in Patients with Severe Acute Respiratory Syndrome or Coronavirus Disease 2019

Abstract: BackgroundSevere acute respiratory syndrome (SARS) and coronavirus disease 2019 (COVID-19) are closely related. The effect of AKI on the clinical outcomes of these two conditions is unclear.MethodsThis retrospective, territory-wide cohort study used an electronic public healthcare database in Hong Kong to identify patients with SARS or COVID-19 by diagnosis codes, virologic results, or both. The primary endpoint was a composite of intensive care unit admission, use of invasive mechanical ventilation, and/or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…A territory-wide, retrospective cohort study was performed using the Clinical Data Analysis and Reporting System (CDARS) managed by Hospital Authority, Hong Kong, with which multiple studies on COVID-19 have previously been conducted. 3 , 4 , 5 , 6 We first identified 41 255 patients with COVID-19 who were hospitalized from January 1, 2022, to March 31, 2022. Of these patients, 12 629 who attended public hospitals with serial cycle threshold (Ct) values measured at least 3 times were included in the analysis (eFigure 1 in Supplement 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A territory-wide, retrospective cohort study was performed using the Clinical Data Analysis and Reporting System (CDARS) managed by Hospital Authority, Hong Kong, with which multiple studies on COVID-19 have previously been conducted. 3 , 4 , 5 , 6 We first identified 41 255 patients with COVID-19 who were hospitalized from January 1, 2022, to March 31, 2022. Of these patients, 12 629 who attended public hospitals with serial cycle threshold (Ct) values measured at least 3 times were included in the analysis (eFigure 1 in Supplement 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…After the exclusions shown in Figure 2, we identified 24 unique cohort studies with ≥ 50 cases of hospitalized patients with COVID-19-related AKI that reported AKI recovery rates (Table 1). 12,14,16,17,20,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] Although -full recovery‖ is variably defined in these studies, the proportion of surviving patients that experience a full recovery by hospital discharge ranges between 19-79%, with the majority of studies reporting that that >50% of survivors experience -kidney recovery‖ by hospital discharge. 16,20,56 Among those with AKI severe enough to require RRT, most survivors can discontinue RRT prior to hospital discharge, with continued dependence on RRT at hospital discharge ranging from 8-34% of surviving patients (Table 1).…”
Section: Unresolved Tubular Injury Contributing To Ckd Riskmentioning
confidence: 99%
“…It was still unclear whether SARS-CoV-2 directly affect the kidney, although renal histopathological analyses of 26 Chinese COVID-19 patients suggested varying degrees of acute tubular injury ( 24 ). The prognosis of COVID-19 patients with acute kidney injury was poor, especially those patients with other underlying diseases ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%